Direct Derivatization vs Aqueous Extraction Methods of Fecal Free Fatty Acids for GC–MS Analysis. Issue 7 (26th May 2015) - Amer, Bashar; Nebel, Caroline; Bertram, Hanne C.; Mortensen, Grith; Dalsgaard, Trine K.
Abstract: A comprehensive and accurate determination of free fatty acids (FFA) is required for fecal metabolomic investigations. The present study compares three aqueous extraction methods (1) ULTRA‐TURRAX ®, (2) whirl mixing and (3) basic ULTRA‐TURRAX extraction of fecal FFA with a direct derivatization approach using ethyl chloroformate as the derivatization reagent before determination by gas chromatography–mass spectrometry. The direct derivatization method resulted in significantly higher estimations ( P < 0.01) of short‐ and long‐chain fatty acids than was the case when applying the aqueous extraction methods using ULTRA‐TURRAX, whirl mixing, or basic ULTRA‐TURRAX extraction before the derivatization step. Thus, avoiding an aqueous extraction before derivatization reduces the loss of volatile short‐chain FFA and the less water‐soluble long‐chain FFA.